IMPLEMENTASI 5S (SEIRI, SEITON, SEISO, SEIKETSU DAN SHITSUKE) TERHADAP PRODUKTIVITAS KERJA PADA PT. EKAPUTRA PRADA INDONESIA DI PEKANBARU - Ryan, Simatupang Sury Febriansyah; Samsir, Samsir; Anggia, Paramitha (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The company is a management function and a collection of people involved in anactivity to achieve a predetermined goal. In practice, companies need resources tocarry out business activities. One of the resources needed to manage the businessactivities of a company is human resources (HR). Human resources have a veryimportant role because without this element the company will not be able to achievethe goals that have been set. Work productivity will be very important in improvingcompany performance, this is because work productivity is a measure of the qualityand quantity of a workforce in a unit of time to achieve results. or work performanceeffectively and efficiently with the resources used. This study aims to see anddetermine the direct effect of 5S implementation on work productivity. Thepopulation in this study were all employees at PT. Ekaputra Prada Indonesia inPekanbaru totaling 45 people, using Multiple Linear Regression. In this study, thesampling method used the Census Technique, which is a sampling technique inwhich the entire population is selected to be a member of the sample so that thesample becomes 45 respondents. The results in this study Seiri, Seiton, Seiso,Seiketsu and Shitsuke have a significant effect on Work Productivity. With themaintenance of space and better organization of the workplace, it will be able toincrease company profits and also enable companies to show potential strengthsand abilities so that the implementation of 5S will provide an increase in workproductivity. Keywords: Seiri, Seiton, Seiso, Seiketsu, Shitsuke and Work Productivity